Thank you for the opportunity to help you with your question!
r(x) = 4x^2
s(x) = 3x
(r.s)x = r(x)*s(x) = 4x^2 *3x = 12x^3
(r+s)x = r(x)+s(x) = 4x^2 + 3x
(r-s)x = r(x)-s(x) = 4x^2 - 3x
(your question is not very much clear .. in case you need to find some thing else please let me know)
You can use my
promo code: Saroj N , while signing up at study pool and enjoy $10
Please find the solution enclosed here with .. In case of any doubt please feel free to ask… Do not forget to best my answer… If you are having some other problem please feel free to contact me for quick & quality services..
Jun 9th, 2015
Are you studying on the go? Check out our FREE app and post questions on the fly!